ANALISIS HUBUNGAN KARAKTERISTIK DEMOGRAFI TERHADAP PENGHASILAN TENAGA KERJA WANITA USAHA MODISTE DI KOTA BANDA ACEH - Fanny Nailufar; Sufitrayati Sufitrayati (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2017)
This research was conducted to answer the problems in the field of entrepreneurship especially couturier business, so it can be the concept of increasing the income of female workers in the couturier business. Data analysis in this research was done by using analysis model of Cross Tabulations (Crosstabs) by using Chi-Square (X²) test. Based on the result of research, it indicated that there was a significant correlation between monthly incomes with age of female workers. The chi-square test (X²) also showed that there was no significant relationship between monthly income and the formal level of female workers. Meanwhile, a significant relationship was shown between monthly income and marital status of female workers. The result of testing using chi-square test also showed that there is a relationship between monthly income and the number of dependents of female workers’ family